2007
DOI: 10.1007/s00125-007-0787-9
|View full text |Cite
|
Sign up to set email alerts
|

ENPP1 K121Q polymorphism and obesity, hyperglycaemia and type 2 diabetes in the prospective DESIR Study

Abstract: Aims/hypothesis We assessed the predictive value of ectonucleotide pyrophosphatase/phosphodiesterase 1 gene (ENPP1) SNPs with regard to the risk of developing obesity and/or type 2 diabetes in a large French general population. Methods We genotyped the ENPP1 SNPs K121Q (rs1044498), IVS20delT-11 (rs1799774) and A/G+1044TGA (rs7754561) in 5,153 middle-aged participants of the Data from an Epidemiological Study on the Insulin Resistance Syndrome (DESIR) cohort. Results At baseline, the K121Q polymorphism was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 50 publications
4
26
0
2
Order By: Relevance
“…Residual heterogeneity may be partially explained by an interaction between genotype and BMI. We did not find any evidence that the other two ENPP1 polymorphisms (which, together with K121Q, define a previously reported haplotype [15]) have an individual effect on diabetes risk, a result that is consistent with a recent population study by the same investigators (23).…”
Section: Enpp1 K121q Meta-analysis In Type 2 Diabetessupporting
confidence: 90%
“…Residual heterogeneity may be partially explained by an interaction between genotype and BMI. We did not find any evidence that the other two ENPP1 polymorphisms (which, together with K121Q, define a previously reported haplotype [15]) have an individual effect on diabetes risk, a result that is consistent with a recent population study by the same investigators (23).…”
Section: Enpp1 K121q Meta-analysis In Type 2 Diabetessupporting
confidence: 90%
“…10,11,49,50 The question of ENPP1's functional importance in OB etiology is complicated by negative results obtained in other association studies. 12,51 The distribution of association signals across the ENPP1 gene locus observed in this study (see Figure 1b) suggests that associations with OB traits (for example BMI and leptin) may be driven by the 3 0 UTR region, and not necessarily by K121Q polymorphism. This hypothesis is supported by several earlier studies that reported associations of OB-related traits with markers in ENPP1 3 0 UTR.…”
Section: Discussionmentioning
confidence: 65%
“…[6][7][8][9] ENPP1 lies on chromosome 6q22-q23 (OMIM#173335) in a region where several independent studies found a linkage peak to OB phenotypes. [10][11][12][13] ENPP1 is an attractive candidate gene for studying OB, as it was proposed as a key player in the etiology of insulin resistance 14,15 and in a recently suggested mechanism underlying defective adipocyte maturation. 16 The ENPP1 product has also been identified as one of the central regulators of extracellular pyrophosphate (ePPi)/phosphate (Pi) equilibrium levels.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent cellular transfection experiment showed that the Q allele was several fold more effective than the K allele in reducing insulin stimulation of IR autophosphorylation, IR substrate-1 phosphorylation, phosphatidylinositol 3-kinase activity, glycogen synthesis and cell proliferation. 18 During the last decade, genetic association studies have found a positive association between K121Q and T2D in Caucasians and Indians, [19][20][21] Tunisians, 22,23 African Americans 24 and Dominicans. 25 The Q allele was also observed to increase the risk of obesity in the Caucasian population.…”
Section: Introductionmentioning
confidence: 99%